EARNING MANAGEMENT DALAM PENAWARAN SAHAM PERDANA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - NOVIUS, ANDRI (STIE Totalwin Semarang, 2011)
This study detected the differences of the company earning before publicly traded, at the moment of publicly traded, and after publicly traded in manufacture entities. The sample was 22 manufacture on Initial Public Offering from 2005 to 2007 by using financial statement during five years The data analyzed by Wilcoxon stage. The result shown that there is the difference before go public and at the moment of publicly traded. So that presence earning management practice by management of entities in order to collect cash from investor. At the moment of go public, there is no difference, because the performance of entities become better and earning management practice fared well